ANALISIS GAYA BELAJAR SISWA PADA PELAJARAN BAHASA INDONESIA PADA KELAS VIII SMP SEKOLAH YAPENDAK KEC. UJUNG PADANG - Nova Mawar Hutabarat; Perida Roma Asi Siahaan (Bahasa Indonesia Prima, 2024)
Lack of understanding of the concept of materia taught to students and teachers do not know each student's learning style. This research aims to determine students' learning styles by analyzing students' learning styles in learning Indonesian in class VIII of SMP Yapendak School, Kec. Ujung Padang for the 2022/2023 academic year. This research is a qualitative descriptive study. The population in this study were all class VIII students of SMP Yapendak School, Kec. Ujung Padang with a total of 82 students. The technique used in sampling was collecting data on student learning styles in the process of learning Indonesian in class SMP Yapendak School, Kec. Ujung Padang used a questionnaire with 30 questions. The results of the research show that the learning style analysis of the visual student learning style indicators has an average percentage of 72%. The auditory learning style indicator has an average percentage of 66%. In terms of kinesthetic student learning style indicators, the average percentage is 65%. So it can be analyzed that students' learning styles in learning Indonesian in class SMP Yapendak School Kec. Ujung Padang is more towards the Visual learning style because it gets a higher average score and percentage compared to audiotorial and kinesthetic learning styles.